VD_FINDINFO Jug / 2022 / 373 vom 2. November 2022 - VD Tribunal cantonal (2022)
ASSUREUR-MALADIE, PRISE EN CHARGE PROVISOIRE DES PRESTATIONS, FOURNISSEUR DE PRESTATIONS | 25 al. 1 LAMal, 32 al. 1 LAMal, 56 al. 2 LAMal